Utilization SAW Method to Choose Goods Suppliers at PT.King Computer - Elvis Pawan; Patmawati Hasan; Rosiyati M.H Thamrin (CCIT Journal, 2020)
The operation of a good system in a company is inseparable from the support of business partners, but it is impossible to obtain if the partner or supplier of goods does not work as the target of the company itself. Given these problems, it is deemed necessary to create a DSS system that can assist directors in determining suitable suppliers to work together. In making this SPK, the SAW method starts from the selection of types of goods, selects criteria and sub-criteria, and determines the weights of each criterion.This study produced an SPK, with six main criteria and their respective weights, based on the criteria entered and processed in accordance with the rules of the SAW method, CV. Eka Makmur was chosen as the most suitable recommendation to become a supplier for all in one PC items. At the testing stage, three methods have been carried out namely black box, output testing, and user acceptance test.